Recurrent Idiopathic Facial Paralysis: A Case Report - Hale Hekim Baloğlu; Serpil Savaş; Feride Ekimler Süslü; Mustafa Tüz (Archives of Rheumatology, 2010)
Idiopathic facial paralysis is the mononeuropathy Multiple recurrences of idiopathic facial paralysis in a patient may be the sign or sympton of a serious illness. therefore; in recurrent cases, family history, systemic diseases and malignancy must be investigated. In this report, a case of recurrent idiopathic facial paralysis is presented. (Turk J Rheumatol 2010; 25: 162-4)